Peran Impulsive Behavior dan E-Marketing Exposure Terhadap Post Purchase Regret Saat Berbelanja Online - Anggita Amanda Putri; Puji Astuti (Economic Reviews Journal, 2025)
Post purchase regret is of particular concern to companies or sellers because it can be a reason for giving negative reviews of products or stores, not wanting to shop again and switching shopping to other places. The research objective is to explore the extent of the relationship between impulsive behavior in online shopping, with e-marketing exposure, attitude towards product, attitude towards price on consumer behavior and its effect on post purchase regret after making a purchase due to online shopping activities. The research population is users of the Shopee, Tokopedia and Lazada application marketplaces in Jabodetabek who have experienced regret in online shopping. The study used purposive sampling method, a sample of 115 respondents. Research data analysis using Structural Equation Modeling (SEM) LISREL. This study produces findings including e-marketing exposure has a positive effect on attitude toward product, then e-marketing exposure has a positive effect on attitude toward price, then attitude toward price does not prove that post purchase regret has an influence, impulsive behavior does not prove that it has a positive influence on post purchase regret. The benefits of research make a positive contribution to science, especially management and marketing strategy, in impulsive behavior and e-marketing exposure and post purchase regret so that the expected output can make a positive contribution to customers, so as not to cause regret. Managerial implications assist marketers in directing more efficient and effective efforts, as well as reducing the risk of unwanted purchase behavior, expanding its focus by identifying e-marketing strategies for various specific demographic market segments. The study's limitation lies in its general focus on evaluating overall regret levels without distinguishing the influence of specific sectors of demographic differences within the consumer population. Keywords: E-Marketing Exposure, Attitude Toward Price, Impulsive Behavior, Attitude Toward Product, and Post Purchase Regret ABSTRAK Post purchase regret menjadi perhatian khusus bagi perusahaan atau penjual karena dapat menjadi alasan untuk memberikan review negatif atas produk atau toko, tidak mau belanja kembali dan berpindah belanja ke tempat lain. Tujuan penelitian untuk mengeksplorasi sejauh mana keterkaitan antara impulsive behavior dalam berbelanja online, dengan e- marketing exposure, attitude toward product, attitude toward price terhadap perilaku konsumen serta pengaruhnya pada post purchase regret setelah melakukan pembelian akibat aktivitas belanja online. Populasi penelitian adalah pengguna marketplace aplikasi Shopee, Tokopedia dan Lazada di Jabodetabek yang pernah mengalami penyesalan dalam belanja online. Penelitian menggunakan metode purposive sampling, sampel sebanyak 115 responden. Analisis data penelitian menggunakan Structural Equation Modelling (SEM) LISREL. Penelitian ini menghasilkan temuan diantaranya e-marketing exposure berpengaruh positif terhadap attitude toward product, selanjutnya e-marketing exposure berpengaruh secara positif terhadap attitude toward price, kemudian attitude toward price tidak membuktikan bahwa post purchase regret memiliki pengaruh, impulsive behavior tidak membuktikan bahwa memiliki pengaruh positif terhadap post purchase regret. Manfaat penelitian memberikan konstribusi positif terhadap keilmuan khususnya manajemen dan strategi pemasaran, dalam impulsive behavior dan e-marketing exposure serta post purchase regret sehingga output yang diharapkan dapat memberikan kontribusi positif terhadap pelanggan, sehingga tidak menimbulkan rasa penyesalan. Implikasi manajerial membantu pemasar dalam mengarahkan upaya yang lebih efisien dan efektif, serta mengurangi risiko terjadinya perilaku pembelian yang tidak diinginkan, memperluas fokusnya dengan mengidentifikasi strategi pemasaran elektronik untuk berbagai segmen pasar demografi tertentu. Limitasi studi ini terletak pada fokusnya yang umum dalam mengevaluasi tingkat penyesalan secara keseluruhan tanpa membedakan pengaruh dari sektor-sektor khusus perbedaan demografis dalam populasi konsumen. Kata Kunci: E-Marketing Exposure, Attitude Toward Price, Impulsive Behavior, Attitude Toward Product, and Post Purchase Regret